Urbanismo e municipalismo na Espanha* IEAL e a articulação Ibero-americana para o desenvolvimento municipal | Urbanism and municipalismo in Spain IEAL and Ibero-american articulations for municipal development - de Faria, Rodrigo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2016)
Este artigo está direcionado ao estudo dos temas e debates que ocorriam no municipalismo espanhol na década de 1950, especialmente em relação à atuação institucional do Instituto de Estudios de Administración Local (IEAL) e seu papel na retomada da construção das articulações internacionais com os países ibero-americanos. Com foco na organização e debates que ocorreram no I Congresso Ibero-americano de Municípios em Madrid no ano de 1955, interesse é analisar o pensamento urbanístico espanhol em suas articulações com o pensamento municipalista, e assim evidenciar as concepções dos profissionais e professores que atuavam na Escuela de Estudios Urbanos do IEAL, especialmente Gabriel Alomar, autor do livro “Teoria de la Ciudad”, certamente base conceitual que orientava a formação dos funcionários públicos para atuarem no campo do urbanismo para o desenvolvimento municipal dentro dos pressupostos da autonomia local. This paper is directed to studying the themes and debates occurred in the Spanish Municipalism in the 1950s, particularly regarding the Instituto de Estudios de Administración Local (IEAL) – Institute of Local Administration Studies, and its role in the construction of international articulations with the Ibero-american countries. Focusing on the organization and debates occurred during the I Congreso Iberoamericano de Municípios (Congress of the Iberoamerican Municipalities) in Madrid in the year of 1955, it aims to analyze the Spanish urbanistic thinking and its articulations with the municipalist thinking, in order to evidence the conceptions of professional and academics of the IEAL’s Escuela de Estudios Urbanos (School of Urban Studies), specially Gabriel Alomar, author of the book “Teoria de La Ciudad” (Theory of the City), certainly the conceptual base that oriented the education of the civil servants to act in the urbanism field for municipal development within the framework of local autonomy.